Efficacy of favipiravir in COVID-19: A retrospective two center comparative study - Tukenmez Tigen, Elif; Mikulska, Malgorzata; Erturk Sengel, Buket; Signori, Alessio; Dettori, Silvia; Tutino, Stefania; Guner, Abdullah Emre; Odabasi, Zekaver; Korten, Volkan; Bassetti, Matteo (The Journal of Infection in Developing Countries, 2024)
Introduction: Favipiravir (FVP) is an antiviral, targeting RNA-dependent RNA polymerase. We aimed to evaluate the efficacy of FVP as a treatment for COVID-19. Methods: We conducted a retrospective study in two centers (San Martino University Hospital in Genova, Italy, and Marmara University Pendik Training and Research Hospital, Turkey). Adult patients (inpatients) diagnosed with COVID-19 between March and June 2020 were included. All patients in the Italian center received the standard of care (SoC) treatment, while in the Turkish center patients received FVP in addition to SoC. Results: Six hundred-nineteen patients were analyzed (225 from Turkey, all treated with FVP, and 394 from Italy, none treated with FVP). Propensity score-matching was done in 142 patients (71 from the SoC group vs. 71 from the SoC + FVP group). A Higher requirement of NIV/CPAP (n = 38; 53.5%) was registered in the SoC group compared to the SoC + FVP group (n = 9; 12.7%). A higher frequency of intubation was registered in the SoC + FVP group (n = 25; 35.2% vs n = 13, 18.3%). There was a trend towards better survival in SoC + FVP treated patients with HR = 0.64 (95% CI 0.30-1.34). At 28 days the OS was, respectively, 70.3% (95% CI: 53.2-82.1) vs 80.3% (95% CI: 69.0-87.8). Conclusions: The addition of FVP to SoC did not show a significant difference in survival and invasive and noninvasive (CPAP/NIMV) mechanical ventilation compared to standard of care in moderate and severe COVID-19-infected patients.